Smart Home Berbasis Internet of Things (IoT) Dalam Mengendalikan dan Monitoring Keamanan Rumah - Supiyandi Supiyandi; Chairul Rizal; Muhammad Iqbal; Muhammad Noor Hasan Siregar; Muhammad Eka (Journal of Information System Research (JOSH), 2023)
Smart Home or smart home is a system built with the help of a computer to integrate and control home devices automatically and efficiently. The development of "Smart Home" technology is the impact of the development of technological advances that aim to help people manage their daily activities in controlling electronic equipment and monitoring the condition of the house. This home automation system was developed with the aim of supporting electricity and water saving programs. Smart home technology developed, both in home automation systems and security will be controlled centrally by the microcontroller. This study aims to build an electronic device control system at several location points automatically by sending SMS from the cellphone to the control module. This device system will also connect the control module via the internet network so that the Internet of Things (IOT) function is built. Arduino-based Smart Home facilitates home security systems by installing Infrared sensors to detect moving objects, MQ-2 Sensors to detect gas leaks, DHT11 Sensors to detect temperature and humidity, Ultrasonic Sensors to measure the water level in water reservoirs.